INSTRUMENTO PARA COLETA DE DADOS RELACIONADOS A SEGURANÇA EM PRENSAS MECÂNICAS E TUPIAS - ENDRUWEIT, ANDREAS A. B.; SCHNEIDER, ANDRESA; SACKSER, GILBERTO; RIBEIRO, LUIS F. M.; DUARTE, LUIZ C. D. S.; ECKHARDT, MOACIR (Salão do Conhecimento, 2013)
Resumo